Towards demand based innovation policy? The introduction of shocks as innovation policy instrument - Tuomo Nikulainen; Antti-Jussi Tahvanainen (The Research Institute of the Finnish Economy (ETLA), 2009)
This paper aims to provide an overview of the recently introduced demand based innovation policy instrument in Finland - the Strategic Centers for Science, Technology and Innovation (in Finnish - SHOKs). SHOKs are formed to support the innovative activities of existing industries in Finland with emphasis on industrial renewal through innovation. The focus in this paper is on the current state of SHOKs, the role of different actors in their formation process, the organization of SHOKs, the development of strategic long-term research agendas and short-term research programs, the challenges related to intellectual property rights, and co-operation between different SHOKs. The paper compares these dimensions across SHOKs and tries to highlight some potential threats and opportunities that might arise. The underlying interview data shows that, while SHOKs are fairly similar in most of the dimensions, there are differences in partner selection, industry specificity, and formulation of research areas. It should be noted that individual SHOKs are in very different stages of development as some have existed for two years and others are still to be established.
Keywords: O31; O32; O33; O34; O38; 330; SHOK; demand-based innovation policy; policy instruments; national systems of innovation; Innovationspolitik; Forschungs- und Technologiepolitik; Forschung; Forschungskooperation; Technologietransfer; Finnland